Business metadata capturing enterprise knowledge - Inmon, William H.; O'Neil, Bonnie K.; Fryman, Lowell (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2008)
People have a hard time communicating, and also have a hard time finding business knowledge in the environment. With the sophistication of search technologies like Google, business people expect to be able to get their questions answered about the business just like you can do an internet search. The truth is, knowledge management is primitive today, and it is due to the fact that we have poor business metadata management. This book is about all the groundwork necessary for IT to really support the business properly. By providing not just data, but the context behind the data. For the IT professional, it will be tactically practical--very "how to" and a detailed approach to implementing best practices supporting knowledge management. And for the the IT or other manager who needs a guide for creating and justifying projects, it will help provide a strategic map. * First book that helps businesses capture corporate (human) knowledge and unstructured data, and offer solutions for codifying it for use in IT and management. * Written by Bill Inmon, one of the fathers of the data warehouse and well-known author, and filled with war stories, examples, and cases from current projects. * Very practical, includes a complete metadata acquisition methodology and project plan to guide readers every step of the way. * Includes sample unstructured metadata for use in self-testing and developing skills.
Business Metadata -- The Quest for Business Understanding -- Section I: Rationale and Planning -- 1. What is Business Metadata -- 2. The Value and Benefits of Business Metadata -- 3. Who is responsible for Business Metadata? -- 4. Business Metadata, Communication and Search (BKO) -- 5. OUT; this chapter rolled into Stewardship -- Section II: How-To -- 6. How do you initiate a MD project? -- 7. Technology Infrastructure for Metadata -- 8. Business Metadata Capture -- 8.5Business Metadata Capture from Existing -- 9. MD Data Delivery -- Section III: Special Categories of Business MD -- 9.5Data Quality -- 10. Semantics & Ontologies -- 11. Unstructured MD -- 12. Business Rules -- 13. Metadata & Compliance -- 14. Knowledge Management and Business Metadata -- Section IV: Putting it All Together -- 15. Summary -- Appendix.
Includes bibliographical references and index.
Keywords: Database management; Metadata; Management information systems; Electronic books